959 Improve the call to action; increasing the impact of falls prevention messages while maintaining the evidence. (1st September 2016) - Wells, Venessa; Anderson, Emily; Piazz, Megan De; Summers, Juliana; Meade, Rachel; Sweeney, Roisin; Crawford, Gemma; Jancey, Jonine
Abstract : Background: Falls amongst adults aged over 60 remains a significant public health issue, requiring effective community-based prevention strategies. In an effort to reduce falls, the Injury Control Council of WA (ICCWA) with the support of the WA Department of Health has promoted the Nine Steps to Stay On Your Feet ® (Nine Steps) message since 2004. The Nine Steps raised awareness of falls prevention strategies through nine messages, three of the messages include: Be Active, Mange Your Medicines and Improve Your Balance. Problem: Research with community members identified the Nine Steps message may be more useful as a falls prevention tool for health professionals rather than for awareness-raising in community members. The results of formative research undertaken to evaluate the effectiveness of the revised messaging and confirm preferred formats are presented. Results: ICCWA sought to reposition the Stay On Your Feet ® message. The objective was to offer positive choices and simplified calls to action that were easy to understand, recall and implement via new messages, writing style, imagery and resources. Research included a rapid literature review; focus groups with community dwelling older adults; consultations with falls prevention clinicians, policy makers and academics; and a review of draft resources against best practice in behaviour change communication. Results emphasised the importance of delivering consistent messages across different settings. Resources should function as reminders and should be accessible, appealing and short with minimal text. Imagery should feature diverse talent who are real and similar to the target audience. Conclusion: Five Improve Move Remove social marketing campaigns are being implemented to promote the revised calls to action: improve your health, move your body and remove hazards. Evaluation of these campaigns is ongoing and will establish the impact of the revised messaging.